Growing Self-Confidence through English Language Training at LKSA Nur Faisal - Nurul Adawia; AN, Andi Yana Fitrah (IJOCSE: Indonesian Journal of Community Services, 2024)
The English language training activities carried out for children at Nur Faisal Children’s Social Welfare Institution are one of the efforts to improve English language skills, especially for 14 children who come from underprivileged backgrounds so that it is carried out free of charge. The implementation of this English training is carried out through an approach that focuses on developing self-confidence in children. This activity is carried out in an interactive and fun way by inviting children to be actively involved and interspersed with games. Children are also given the opportunity to practice speaking or conversing with their friends, expressing greetings and increasing vocabulary by mentioning the names of objects in English. With this activity, it can increase children’s enthusiasm in practicing English with confidence to eliminate the fear of speaking in front of others. Therefore, the training for children at LKSA Nur Faisal provides new knowledge in improving their ability to speak in English and also increases their confidence to establish themselves to achieve future goals. Preparations made before the English language training included preparing materials and determining the time and place of the activity. As a result of the training, many children were able to recognize objects around them and were able to greet people using English, as well as pronunciation in the language.